Smokers Paradox Phenomenon and Impact of Pharmacists’ Smoking Cessation Counselling in Acute Myocardial Infarction Patients - Aravamuthan, Anandhasayanam; Vijayan, Sharmia; Anbarasan, Poovarasan; Sakthivel, Sathish Kumar; Sagadevan, Sundaramoorthy; Velumani, Sarmatha; Kannan, Subramaniyan; Balakrishnan, Sangameswaran (Indian Journal of Pharmacy Practice)
Background: The “smoker’s paradox” suggests that smokers may have better outcomes following Acute Myocardial Infarction (AMI) than non-smokers. However, this paradox remains controversial. This study aimed to evaluate the paradox by comparing clinical outcomes between chronic smokers, former smokers and non-smokers with AMI and to assess the impact of pharmacists’ smoking cessation counselling. Materials and Methods: A prospective interventional study was conducted at Sudha Institute of Medical Sciences, Erode, involving 218 AMI patients. Data were collected on rehospitalization, recurrent Myocardial Infarction (MI), mortality, and comorbidities. The study population was divided into chronic smokers, former smokers and non-smokers. Statistical analyses, including the chi-square test and Mann-Whitney U test, were used to evaluate the differences in patient outcomes and the effectiveness of smoking cessation counselling. The follow-up period assessed smoking cessation at day 90. Results: Chronic smokers had significantly worse outcomes compared to non-smokers, including higher mortality (37.6% vs. 23.5%, p<0.05), recurrent MI (47.7% vs. 28.2%, p<0.05), and rehospitalization rates. When female patients were excluded, these differences became more pronounced, with higher mortality (37.6% vs. 20%, p<0.05) and recurrent MI (47.7% vs. 25%, p<0.05). Former smokers had better outcomes than chronic smokers but fared worse than non-smokers. Smoking cessation counselling showed positive effects, with 30.8% of patients quitting smoking by day 90 (p=0.008). Conclusion: Contrary to the smoker’s paradox, chronic smokers experienced poorer short- and long-term outcomes post-AMI. Smoking cessation interventions, especially pharmacist-led counselling, improved patient outcomes, highlighting the need for continued efforts to reduce smoking in AMI patients.
Keywords: Acute Myocardial Infarction (AMI); Smokers Paradox; Smoking Cessation; Pharmacist Intervention; Rehospitalisation; Mortality Rate; Recurrent Myocardial Infarction (MI)